Atlas of Neoplastic Pulmonary Disease Pathology, Cytology, Endoscopy and Radiology - Fraire, Armando E.; Cagle, Philip T.; Irwin, Richard S.; Mody, Dina R.; Ernst, Armin; Blackmon, Shanda; Allen, Timothy Craig; Dishop, Megan K.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Atlas of Neoplastic Pulmonary Disease: Pathology, Cytology, Endoscopy and Radiology is a unique atlas that provides images from four major disciplines involved in the study and diagnosis of lung tumors. This atlas, containing 41 chapters represents a wide range of neoplastic lung entities and will be a quick and reliable interdisciplinary tool for the practitioner involved in the management of lung tumors.
Tumors of Childhood -- Lymphangiomatosis -- Pleuropulmonary Blastoma -- Congenital Pulmonary Myofibroblastic Tumor -- Benign Epithelial Tumors -- Alveolar Adenoma -- Uncommon Endobronchial Surface Tumors -- Salivary Gland Tumors (Benign and Malignant) -- Mucous Gland Adenoma -- Pleomorphic Adenoma -- Mucoepidermoid Tumor -- Adenoid Cystic Carcinoma -- Mesenchymal Tumors (Benign and Malignant) -- Inflammatory Polyps -- Inflammatory Pseudotumor -- Pulmonary Chondroma -- Pulmonary Hamartoma -- Localized Fibrous Tumor -- Lipomas and Liposarcomas -- Cystic Lymphangioma -- Lymphangioleiomyomatosis -- Epithelioid Hemangioendothelioma -- Pulmonary Artery Sarcoma -- Synovial Sarcoma -- Lymphoid Neoplasms -- Marginal Zone B-Cell Lymphoma (Maltoma) -- Diffuse Large B-Cell Lymphoma -- Lymphomatoid Granulomatosis -- Langerhans Cell Histiocytosis -- Carcinoid Tumors -- Typical and Atypical Carcinoids -- Miscellaneous Tumors -- Teratoma -- Melanoma -- Thymoma -- Glomus Tumor of the Lung -- Sclerosing Hemangioma -- Preinvasive Disease -- Preinvasive Disease -- Common Major Malignant Epithelial Tumors -- Squamous Cell Carcinoma -- Adenocarcinoma -- Large Cell Carcinoma -- Small Cell Carcinoma -- Less Common Malignant Epithelial Tumors -- Adenosquamous Carcinoma -- Bronchioloalveolar Carcinoma -- Large Cell Neuroendocrine Carcinoma -- Sarcomatoid Carcinoma -- Pulmonary Blastoma -- Metastatic Tumors -- Metastatic Tumors.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology